ISOLASI DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA METABOLIT SEKUNDER DARI EKSTRAK METANOL DAUN MARPUYAN (Rhodamnia cinerea Jack.) - Musyirna Rahmah Nst; Dwi Andreyas; Rahma Dona; Emrizal; Emma Susanti; Ihsan Ikhtiarudin; Rahayu Utami (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
A study on isolation and antibacterial activity of secondary metabolites from the methanol extract of Marpuyan (Rhodamnia cinerea Jack.) Leaves on Escherichia coli has been carried out. Isolation was carried out by column chromatography methods. Whereas the antibacterial activity test was carried out using agar diffusion method. The results of the isolation produced 17.9 mg of RC-F13 isolate compound in the form of light yellow crystals, with a melting point of 170-172oC and soluble in methanol. The results of identification of RC- F13 isolate compounds through testing with AlCl3 reagents, positive including the flavonoid group, were strengthened by the results of the UV spectrum and FT-IR spectrum. Based on the results of the UV spectrum, it was seen that the RC- F13 isolate compound showed λ max 353.60, 257.00 and 209.20 nm. The FT-IR spectrum shows the presence of several functional groups such as OH, C aliphatic C-H, C = O carbonyl, C = C aromatic and C-O. testing the antibacterial activity of methanol extract with a concentration of 20%; 10%; 1%; 0.1% and 0.01%, fraction 13 at 1% concentration; 0.1% and 0.01% and RC- F13 isolate compound concentration of 0.1%, against Escherichia coli bacteria did not show any antibacterial activity which was marked by the absence of clear areas around the disc.